(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Vaccination is one of the most effective preventive measures in modern medicine, playing a crucial role in protecting human health from infectious diseases. This paper discusses the medical and biological significance of vaccination, the immune system’s response to vaccines, and their role in disease prevention. Vaccines stimulate the immune system by introducing weakened or inactivated antigens, leading to the production of specific antibodies and memory cells. This process enables the body to respond rapidly and effectively when exposed to real pathogens in the future. The study highlights the importance of vaccination in reducing morbidity, complications, and mortality rates among both children and adults. In addition, the role of modern biotechnology in developing safe and effective vaccines is examined. Vaccination is essential for strengthening immunity, controlling infectious diseases, and ensuring the formation of a healthy society.